Impact networks : create connection, spark collaboration, and catalyze systemic change. - Ehrlichman, David (Berrett-Koehler, 2021)
"Solving complex problems like climate change or homelessness demands intense collaboration between diverse organizations and individuals. This book offers a powerful tool for facilitating coordinated action"--